2015
DOI: 10.18537/mskn.06.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación antropométrica de los preescolares de la zona urbana en Cuenca, Ecuador

Abstract: Fecha de recepción: 25 de septiembre de 2015 -Fecha de aceptación: 31 de octubre 2015 RESUMENSe realizó un estudio transversal que incluyó 577 preescolares que acudieron a control del niño sano. Se excluyó a niños con patología. Se estudió peso, talla e IMC, según subgrupos de edad y sexo. Se obtuvieron frecuencias absolutas y relativas para las variables cualitativas; promedio y DE para las variables cuantitativas. Se determinó la comparabilidad de grupos según sexo (χ 2 , p>0.05) y edad (U de Mann-Whitney, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
0
0
1
Order By: Relevance
“…The results obtained in the present study confirm the coexistence of deficit and excess malnutrition states, such as stunting and overweight in children of early age in a high-altitude area of northwestern Argentina. Similar results to those obtained here were reported in several articles conducted in different regions of Latin America [21][22][23][24] including Argentina [25]. These studies indicated the coexistence of stunting and excess weight (double burden of malnutrition) present in high altitude areas in recent years, regardless of the percentages obtained by the authors mentioned.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained in the present study confirm the coexistence of deficit and excess malnutrition states, such as stunting and overweight in children of early age in a high-altitude area of northwestern Argentina. Similar results to those obtained here were reported in several articles conducted in different regions of Latin America [21][22][23][24] including Argentina [25]. These studies indicated the coexistence of stunting and excess weight (double burden of malnutrition) present in high altitude areas in recent years, regardless of the percentages obtained by the authors mentioned.…”
Section: Discussionsupporting
confidence: 92%
“…Asimismo, un 14% y 16% de los episodios de infecciones respiratorias agudas (IRA), así como un 3% y 4% de los casos de enfermedad diarreica aguda (EDA) se asocian a desnutrición en estos dos países. En términos de sus efectos en educación, se observó que el 32% de la repitencia escolar en Ecuador y el 16% de ésta en México se asocia a desnutrición sufrida antes de los cinco años de edad (Encuesta Nacional de Salud y Nutrición, 2012; Black et al, 2013;Díaz Granda & Huiracocha Tutivén, 2015;CEPAL, 2017).…”
Section: Desarrollounclassified